Escalating placenta invasiveness: repeated placenta accreta at the limit of viability - Greenbaum S; Khashper A; Leron E; Ohana E; Meirovitz M; Hershkovitz R; Erez O (Dove Medical Press, 2016)
Shirley Greenbaum,1 Alla Khashper,2 Elad Leron,1 Eric Ohana,1 Mihai Meirovitz,1 Reli Hershkovitz,1 Offer Erez1 1Department of Obstetrics and Gynecology, 2Department of Radiology, Soroka University Medical Center, School of Medicine, Ben-Gurion University of the Negev, Be’er Sheva, Israel Abstract: Placenta percreta is an obstetric condition in which the placenta invades through the myometrium. This is the most severe form of placenta accreta and may result in spontaneous uterine rupture, a rare complication that threatens the life of both mother and fetus. In this case report, we describe a 32-year-old woman in her fourth pregnancy, diagnosed with repeated placenta accreta, which was eventually complicated by spontaneous uterine rupture at 24 weeks’ gestation. This patient had a history of abnormal placentation in prior pregnancies and previous uterine injuries. This case demonstrates a pattern of escalating placental invasiveness, and raises questions regarding the process of abnormal placentation and the manifestation of uterine rupture in scarred uteri. Keywords: placenta percreta, uterine injury, laparoscopy, dilatation and curettage, residua, cesarean section scar, spontaneous uterine rupture